Constructing Effective Network Political Communication: Theoretical Models and Ukrainian Practices - Kostyrev, Andrey (Politologija, 2025)
This article explores the construction of effective social networks for political communication, by combining theoretical modeling with empirical validation through practices adopted by Ukrainian officials. It introduces a framework grounded in structural functionalism, social network constructivism, and normative value approaches with the objective to evaluate the role of trust, engagement, and network structure in enhancing communication effectiveness. The article proposes valuence as a metric for assessing the influence of political actors within online platforms and validates its applicability by using case studies of Telegram and Viber channels. The article’s findings reveal that well-designed network configurations, by balancing centralization for trust-building and decentralization for engagement, can significantly enhance political communication outcomes. The study contributes to the theory and practice of networked political communication, offering actionable insights for policymakers and practitioners.